La difícil construcción de la comunidad política - Haya de la Torre, Agustín (2005)
Different antidemocratic discourses are obstacles to consolidate a democratic system. They represent one of the main factors have blocked the setting of a lasting political community in Peru. This paper analyzes both the phenomenon and the history of dictatorial discourses: fascist, indigenist, multiculturalist, and neoliberalist discourses and also those from ‘Sendero Luminoso’ and the radical left. Political positions presuming to possess the absolute truth are criticized. With a sterile confrontation of ‘truths’ is not possible to develop a politic based on consensus among the principal actors which guarantees that consensus is worth beyond a period of any particular government. The text purposes a deep study of the historical causes of authoritarianism and promotes a culture of tolerance and pluralism in order to consolidate the political society.